Pengenalan Investasi Akhirat Melalui Gerakan Nabung Wakaf untuk Generasi Milenial - Billah, Zahida Itisoma (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This study aims to look at the phenomenon of a millennial generation`s behavior in addressing the issue of cash waqf through the application of saving waqf provided by Islamic banking. Era 4.0 is marked by the rapid development of technology and information. One of the main actors / usser who play an active role is the Millennial generation. This generation plays a very important role. Especially in the fields of economic and financial digitization. To create a millennial generation that has a spiritual, productive and innovative spirit, Islamic banking launches a waqf savings application via smartphone. From this research, it is known that many stakeholders must play a role in introducing waqf savings, including institutional approaches, educational institutions, philanthropic institutions, approaches to millennials themselves in addressing and absorbing information, and government agencies as regulators, namely KNKS and the Indonesian Waqf Board ( BWI). Abstrack: Waqf Savings, Millennial Generation, Investment